Body image in breastfeeding women with depressive symptoms: a prospective study. (3rd March 2016) - Zanardo, Vincenzo; Volpe, Francesca; Giustardi, Arturo; Canella, Alessandra; Straface, Gianluca; Soldera, Gino
Abstract: The purpose of this prospective study was to investigate the relationship between body image perception and breastfeeding in puerperae with postpartum depression symptoms. The participants (147 healthy puerperae) completed The Edinburgh Postnatal Depression Scale (EPDS) and the Body Uneasiness Test (BUT-A and BUT-B), investigating body image perception and specific worries about particular body parts or functions. One month after discharge, new mothers participated in telephone interview concerning postpartum lactation practices. The subset of puerperae with EPDS score >9 also participated in psychological EPDS and BUT 6-month follow up. Mothers with EPDS score >9 (28/147, 19.04 %) had significantly higher scores on BUT-A Global Severity Index (0.69 ± 0.64 versus 0.37 ± 0.31, p  < 0.0001) and on BUT-B Positive Symptom Distress Index (0.74 ± 0.57 versus 0.41 ± 0.42, p  < 0004). In addition, the mothers with symptoms of depression were more likely (1:2) to interrupt full breastfeeding in the first month postpartum. At the 6-month follow up, the subset of new mothers with depression symptoms maintained elevated BUT-A and BUT-B scores, while EPDS >9 persisted in one-third of these. In conclusion, mothers with symptoms of depression have longlasting negative body image perception, persistent depressive symptoms, and they interrupt early full breastfeeding.